Influence of Aging Processes on the Characteristics of Power LEDs Soldered Using Composite Solder Pastes - Krzysztof Górecki; Przemysław Ptak; Agata Skwarek (Applied Sciences)
In this paper, the issue of an aging process’s influence on power LEDs’ properties is considered. Some measured DC characteristics of these devices and their thermal and optical parameters obtained are presented after considering different values of the aging process’ duration. Components soldered using different metal–ceramic composite pastes, e.g., with TiO2, were tested. The tested devices and the used measurement setup are described. The measurement procedure is described in detail. The obtained measurement results are discussed. It is shown that after the aging process at elevated temperatures, worse properties were observed for the power LEDs soldered using classical SACX0307 alloy. Most of the samples soldered with reference alloy (not composite) were damaged during the test. The best properties were obtained for the samples soldered with solder paste with the addition of titanium oxide.